Providing Medical Care for Patients with Cardiac Arrhythmias in the Context of the COVID-19 Pandemic. Analysis of the Situation and Personal Experience - Yu. I. Karpenko; V. I. Kushnirenko; A. A. Yarovenko; N. V. Pavlinova; O. I. Bokhonko (Ukrainian Journal of Cardiovascular Surgery, 2021)
The sudden spread of the virus and the rapid increase in the number of patients infected with coronavirus could not but affect the work of cardiology and cardiac surgery departments, catheterization laboratories, electrophysiol-ogy laboratories, in which surgical treatment of cardiac arrhythmias is performed.After the announcement of quarantine in Ukraine, our department of arrhythmias introduced a set of measures to prevent infection of the staff and patients. All operations are carried out in full compliance with epidemic rules. Every patient, even with a negative PCR test, is considered conditionally infected. This allowed the entire staff to work for a long period with a minimal risk of infection and to maintain an uninterrupted cycle of specialized care for patients with cardiac arrhythmias in the city of Odessa, the Odessa region.In accordance with the recommendations of the European Society of Cardiology, we urgently developed and com-municated to all cardiologists, emergency doctors, general practitioners clear criteria for the “urgency” of patients with arrhythmias and indications for hospitalization.We were able not only to reduce the total number of operations, but even to increase in comparison with last year and perform the largest number of operations for cardiac arrhythmias and conduction disturbances in all the years of our work: 856 procedures in one operating room compared to 828 operations in 2018 and 798 operations in 2019.The “golden rule” during the coronavirus pandemic is to carry out surgical treatment on the day of admission, i.e. “one-day operation”.During the pandemic, as a result of the limited availability of consultative and diagnostic assistance to patients with cardiovascular diseases, it is necessary to look for new forms of interaction between the medical care system and the pop-ulation. We carried out 13 trips to the districts of the Odessa region with our equipment (expert class echocardiograph, ECG recorder). 1287 patients were consulted, 496 complete echocardiographic examinations and 1112 ECG recordings were performed.Cardiologists, arrhythmologists and electrophysiologists should actively use all the possibilities of virtual consulta-tions in patients with arrhythmias. In this unprecedented time, it is imperative that patients with cardiac arrhythmias should not feel left out by doctors and the health care system as a whole.In crisis periods of strict quarantine, it is necessary to transfer consultative and diagnostic assistance to the regions: “the doctor goes to the patient”.